Clinical and Genomic Landscape of FGFR3 Alterations Across Different Stages of Urothelial Cancer - Maximilian Haas; Roman Mayr; Danijel Sikic; Bernd Wullich; Niklas Klümper; Philipp Erben; Ralph Wirtz; Christian Bolenz; Florian Roghmann; Robert Stöhr; Veronika Bahlinger; Arndt Hartmann; et al. (European Urology Open Science)
Background and objective: Our aim was to provide a comprehensive analysis of the prevalence of potentially targetable activating FGFR3 alterations and their impact on oncological outcomes across different urothelial carcinoma (UC) stages. Methods: We retrospectively analyzed clinical data and FGFR3 results for 1509 formalin-fixed, paraffin-embedded tissue specimens. Actionable activating FGFR3 mutations were assessed using a well-established multiplex SNaPshot polymerase chain reaction approach. FGFR3 fusion testing was performed with a Qiagen Therascreen kit. Key findings and limitations: In the study population of 1509 patients, 202 (13%) had stage pTa, 380 (25%) had stage pT1, 258 (17%) had localized muscle-invasive bladder cancer (MIBC), 556 (37%) had locally advanced MIBC, 91 (6.0%) had metastatic UC of the bladder (mUCB), and 22 (1.5%) had metastatic upper tract UC (mUTUC). Of the FGFR3 alterations detected in 373 patients (25%), 104 (52%) were in stage pTa, 158 (42%) were in pT1, 42 (16%) were in localized MIBC, 53 (9.5%) were in locally advanced MIBC, nine (9.9%) were in mUCB, and seven (32%) were in mUTUC. FGFR3 alterations were associated with better progression-free survival and overall survival in the overall population (p < 0.001), but not in subgroup analyses for different disease stages. Study limitations include the retrospective design and heterogeneous patient cohort. Conclusions and clinical implications: FGFR3 alterations occur at a stage-dependent frequency and are more prevalent in lower tumor stages. We were unable to demonstrate an independent prognostic effect of FGFR3 alterations on oncological outcomes after adjusting for tumor stage. Patient summary: We analyzed a protein called fibroblast growth factor receptor 3 (FGFR3) in patients with cancer of the urinary tract. We found that more aggressive tumors had fewer genetic changes in FGFR3 in comparison to less aggressive tumors. However, genetic changes in FGFR3 were not related to survival for these patients.